2021
DOI: 10.1002/mnfr.202100067
|View full text |Cite
|
Sign up to set email alerts
|

Soyasaponin A2 Alleviates Steatohepatitis Possibly through Regulating Bile Acids and Gut Microbiota in the Methionine and Choline‐Deficient (MCD) Diet‐induced Nonalcoholic Steatohepatitis (NASH) Mice

Abstract: Scope: Nonalcoholic steatohepatitis (NASH) is a chronic progressive disease with complex pathogenesis of which the bile acids (BAs) and gut microbiota are involved. Soyasaponins (SS) exhibits many health-promoting effects including hepatoprotection, but its prevention against NASH is unclear. This study aims to investigate the preventive bioactivities of SS monomer (SS-A 2 ) against NASH and further clarify its mechanism by targeting the BAs and gut microbiota. Methods and Results: The methionine and choline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 89 publications
7
27
0
Order By: Relevance
“…The increased abundances of Bacteroidetes , Proteobacteria and Verrucomicrobia after mAPS administration agreed with the findings of a previous study. 43 In addition, the Desulfovibrionaceae were increased by mAPS, studies have shown that the alleviating effect of Soyasaponins A2 against methionine and choline deficient (MCD) diet-induced steatohepatitis is accompanied by increased abundance of Desulfovibrionaceae , 44 which is an anti-inflammatory bacteria and sulfate-reducing bacteria. 45 Similar finding was also demonstrated in the mitigating effect of Val-Val-Tyr-Pro (VVYP) peptide against non-alcoholic steatohepatitis, in which the abundance of Desulfovibrionaceae was also increased.…”
Section: Discussionmentioning
confidence: 99%
“…The increased abundances of Bacteroidetes , Proteobacteria and Verrucomicrobia after mAPS administration agreed with the findings of a previous study. 43 In addition, the Desulfovibrionaceae were increased by mAPS, studies have shown that the alleviating effect of Soyasaponins A2 against methionine and choline deficient (MCD) diet-induced steatohepatitis is accompanied by increased abundance of Desulfovibrionaceae , 44 which is an anti-inflammatory bacteria and sulfate-reducing bacteria. 45 Similar finding was also demonstrated in the mitigating effect of Val-Val-Tyr-Pro (VVYP) peptide against non-alcoholic steatohepatitis, in which the abundance of Desulfovibrionaceae was also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that BA metabolism is associated with liver disease and may be a potential target for its treatment ( Jung et al, 2021 ). Many natural products have been shown to alleviate or prevent NAFLD by regulating BA metabolism ( Huang et al, 2019 ; Xiong et al, 2021 ). In the present study, IsA effectively ameliorated hepatic steatosis and related metabolic dysfunctions in HFD-induced NAFLD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Soyasaponins are a family of phytochemical saponins that are present mainly in soybeans and other legumes (e.g., lentils and green peas) [ 52 ]. On average, soybean and its products contain soyasaponins at a content of about 0.17~6.16% [ 53 ]. Soyasaponins are amphiphilic oleanane triterpenoid glycosides with sugar moieties (polar side chains) attached to aglycone (a nonpolar pentacyclic ring).…”
Section: Soyasaponinsmentioning
confidence: 99%
“…Second, soyasaponins can ameliorate inflammation, which is another key mediator in the pathogenesis of AS. In recent years, the anti-inflammatory activities of soyasaponins have been intensively investigated in different inflammatory models of cells and animals [ 11 , 53 , 54 , 62 ] and well reviewed [ 52 , 57 ]. The evidence regarding soyasaponins’ anti-inflammatory activities in macrophages can to a great extent support that soyasaponins may have potentials in the prevention of AS, because macrophages are one of the major players in the pathogenesis of AS.…”
Section: Soyasaponinsmentioning
confidence: 99%